Counter Narrative of Irrigation Management: The Case of Pakistan - Gadi, Mushtaq (Water Nepal, 2003)
Historical trends show that irrigation management in the Indus basin region has not been simply a matter of economic benefit, but has also been connected with political as well as ecological imperatives. In order to take these imperatives into account, there is a need to find alternative solutions based on new policy linkages among rights, including historical rights, democratic governance and sustainable modes of water use. The revival of traditional water harvesting systems should be part of this new thinking and strategy.Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.269-276